A gestão do conhecimento e o repositório institucional da Universidade Federal do Tocantins - Francisco Gilson Rebouças Porto Junior; Edson de Sousa Oliveira (Desafios, 2016)
The article discusses the project of creation and implementation of the Institutional Repository of the Federal University of Tocantins, RIUFT. The goal is to gather, store, organize, preserve, retrieve and disseminate scientific and academic production of UFT with a view to the management of scientific information, increasing the visibility and prestige of the institution in the national and international levels. Search available to the university community a space to store and preserve the information produced in the institution and at the same time promoting the transparency of public spending and support for research activities and creation of scientific knowledge within the UFT. The implementation of RIUFT is through adherence to Ibict the notice, and will be developed in two phases: planning and implementation. This study also addresses a history of actions implemented by Ibict in favor of open access movement to scientific knowledge as well as a brief literature review of the knowledge society and information and communication technologies. As a research technique, we adopted a qualitative approach, using literature review and exploratory research. The data collection method adopted was based on information provided by the university and its graduate programs.